No Emancipation without Compensation : Slave Owners’ Petitions and the End of Slavery in the Netherlands, c. 1833-1873 - Lauret, Lauren (BMGN - Low Countries Historical Review, 2024)
This article analyses how Dutch slave owners and shareholders used petitions to influence how slavery was abolished in Suriname, Curaçao and the Antilles. They have been characterised as defenders of slavery. Throughout this article it will become clear that slave owners and shareholders did not aim for the continuation of slavery in the Dutch Atlantic after the 1840s. Instead, they successfully lobbied to postpone abolition until the most favourable conditions for them – rather than the enslaved people – had been agreed in Parliament. British legislation and colonial practices inspired their advocacy for financial compensation and labour immigration, showing the transnational nature of this approach. Referring to legislation adopted by the States General also proved an effective tactic to legitimise their claims. The resulting Emancipation Act became part of the Dutch State’s transformation into an anti-slavery empire, because the Act expanded the state’s power over the formerly enslaved people in Suriname and the use of coerced labour under the guise of abolition.